DESIGN, SYNTHESIS, MOLECULAR DOCKING, AND BIOLOGICAL EVALUATION OF PYRAZOLE 1-CARBOTHIAMIDE INCORPORATED ISOXAZOLE DERIVATIVES - RADHIKA TUMMA; HARINADHA BABU VAMARAJU (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objectives: Novel isoxazole incorporated pyrazole carbothiamide 5 (a-r) was designed and synthesized, docked and evaluated for anticancer activity Michigan Cancer Foundation-7 (MCF-7), and breast cancer cell lines. Materials and Methods: Designed compounds were synthesized by the condensation of 1-(5-methyl-3-(4-nitrophenyl) isoxazole-4-yl) -3-(substitutedphenyl) prop-2-en-1-one (4) with thiosemicarbazides and substituted thiosemicarbazides to give the target molecules 5 (a-r). To predict the affinity and activity of the ligand molecule, the docking program Accelrys Discovery Studio 2.1 was employed to generate different bioactive binding poses of designing molecules at the active site of human Dihydrofolate Reductase (DHFR) (PDB ID: 1KMS). All the synthesized compounds were characterized based on the spectral and elemental analysis data. Antiproliferative activity was performed against MCF-7 breast cancer cell lines. Results: All the synthesized compounds showed the characteristic peaks in Fourier-transform infrared,1H C13NMR, and mass spectral analysis. During docking, all the synthesized compounds 5 (a-r) exhibited higher fitness scores with minimum three bonding interaction with the active site human DHFR (PDB ID: 1KMS). In the MTT assay based on MCF-7 breast cancer cell lines, most of the compounds exhibited significant activity. In the antiproliferative assay against MCF-7 cell lines, most of the compounds exhibited potent activity with IC50 values in micromolar concentrations. Compounds 5a, 5b, 5f, 5h, and 5k have exhibited significant anticancer activity. Conclusions: The derivatives were synthesized in quantitative yields. New derivatives possess the antiproliferative activity and antitubercular activity.